2021
DOI: 10.1038/s41467-021-26943-z
|View full text |Cite
|
Sign up to set email alerts
|

Sea-ice derived meltwater stratification slows the biological carbon pump: results from continuous observations

Abstract: The ocean moderates the world’s climate through absorption of heat and carbon, but how much carbon the ocean will continue to absorb remains unknown. The North Atlantic Ocean west (Baffin Bay/Labrador Sea) and east (Fram Strait/Greenland Sea) of Greenland features the most intense absorption of anthropogenic carbon globally; the biological carbon pump (BCP) contributes substantially. As Arctic sea-ice melts, the BCP changes, impacting global climate and other critical ocean attributes (e.g. biodiversity). Full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 103 publications
4
72
1
Order By: Relevance
“…A recent study reported that anomalous reduction of sea ice concentration and extreme deep mixed layers occurred northeast of Fram Strait in the 2017/2018 winter 48 . Another study pointed out that the anomalous ocean stratification in 2018 affected local biogeochemical cycles north of the Fram Strait 49 . The anomalous ice melt reported here can have contributed to the reduction of sea ice cover in this area, while the southerly winds can have advected the meltwater eastward by Ekman transport and contributed to the observed fresher surface layer and shallower warm AW layer observed in the western Eurasian basin in winter 2017 21 .…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that anomalous reduction of sea ice concentration and extreme deep mixed layers occurred northeast of Fram Strait in the 2017/2018 winter 48 . Another study pointed out that the anomalous ocean stratification in 2018 affected local biogeochemical cycles north of the Fram Strait 49 . The anomalous ice melt reported here can have contributed to the reduction of sea ice cover in this area, while the southerly winds can have advected the meltwater eastward by Ekman transport and contributed to the observed fresher surface layer and shallower warm AW layer observed in the western Eurasian basin in winter 2017 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The western part of the North Atlantic Ocean near Baffin Bay and the Labrador Sea (Canadian Arctic) and the eastern part, at the Fram Strait and the Greenland Sea, exhibit the “most intense absorption of anthropogenic carbon globally” [ 20 ], and the biological carbon pump plays a key role. In the Canadian Arctic, the abundance of picophytoplankton in the photic zone, specifically Micromonas , has been shown to be increasing due to the influence of climate change at the same time as larger phytoplankton decline [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…This patterning connects to physical dynamics in that coexistence and even enhancement are seen in frontal regions (where the intermingling of water masses occurs) and dominances seemingly arise in water masses with more coherent origins and characteristics. Additionally, the eddying recirculation observed in this area of the Fram Strait could transport species adapted to cold waters towards warmer waters, and vice versa [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations